The effects of military-wide introduction of advanced tourniquets in the Israel Defense Forces. Issue 5 (May 2020) - Tsur, Avishai M.; Nadler, Roy; Benov, Avi; Glassberg, Elon; Siman-Tov, Maya; Radomislensky, Irina; Bodas, Moran; Peleg, Kobi; Thompson, Patrick; Fink, Noam; Chen, Jacob
Highlights: The Israel Defense Forces completed a military-wide introduction of advanced tourniquets. The rate of tourniquet application increased more than four-fold. As of 2016, there were no recorded cases where the old tourniquets were applied. There was no increase in the in-hospital amputation rate. Abstract: Background: Early application of tourniquets has reduced injury death rates. At the end of 2013, the Israel Defense Forces Medical Corps completed a military-wide introduction of the Combat Application Tourniquet as the standard-issued tourniquet. The accompanying clinical practice guideline encouraged combat soldiers and medical teams towards a liberal use of tourniquets for extremity injuries, even when in doubt. Objectives: This study aimed to assess the effects of the wide introduction of advanced tourniquets on the rate of tourniquet applications, the type of tourniquet applied, and the differences in hospitalisation outcomes following the introduction. Methods: The study population was composed of hospitalised military casualties with an extremity injury treated by military medical teams between 2006 and 2015. Prehospital data were extracted from the Israel Defense Forces Trauma Registry and matched to corresponding hospital data from the Israeli National Trauma Registry. Two periods were compared: 2006–2013 "pre-intervention period" and 2014–2015 "post-intervention period". Results: A total of 1, 578 casualties were recorded during the study period. Of these, 320 (20.3%) occurred between 2014–2015. Characteristics of casualties in the post-intervention period were similar to those in the pre-intervention period including the rate of traumatic amputations (2.5% vs 2.2%, p = 0.93) and Injury Severity Score of 16 or above (12.8% vs 14.9%, p = 0.40). The rate of tourniquet application was more than four-fold in the post-intervention period compared to the pre-intervention period (22.8% vs 5.5%, p < 0.001). Nevertheless, rates of in-hospital amputations (1.6% vs 1.6%, p = 1.00) and death (0.9% vs 1.3%, p = 0.53) were similar in the two periods. Conclusion: Following the IDF military-wide introduction of advanced tourniquets, the tourniquet application rate rose sharply, the use of old tourniquets ceased over time, and in-hospital amputation rate did not increase. These findings suggest that the awareness for haemorrhage control using advanced tourniquets rose.